Peran Bahasa (Indonesia) Dalam Menjaga Keberlanjutan Lingkungan Hidup - Abdul Hamid (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
Sustainable development goals (SDGs) are not something new. SDGs has been going on for a very long time, both nationally and internationally. One of the goals of sustainable development is about the environment, about achieving sustainable management of natural resources and the environment as a support for all life. Various issues related to the environment are still ongoing. The waste problem is still being discussed, so in 2020 the government will issue regulations regarding waste management. In Indonesian, the jargon has long been known, "Buanglah sampah pada tempatnya!" and the ban “Jangan membuang sampah sembatrangan!” It turns out that this jargon has been "deliberately" formally instilled in children's minds from the past until now through textbooks issued by the government. In both jargons it turns out that there is inappropriate treatment of waste. Therefore, until now waste is still a problem for us.